SENSORY REPRESENTATION SYSTEMS OF NLP ON CONSUMERS’ RESPONSES TO CELEBRITY ENDORSEMENT - Novalia Rahma Dhani; Rita Hartati (Bajang Institute, 2024)
The sensory representation system is how people perceive what comes in through the three senses, visual, auditory, and kinaesthetic (Vaknin, 2008). This study aims to analyze the sensory representation systems in neuro-linguistic programming (NLP) found in consumers’ responses to celebrity endorsement Nagita Slavina in a post on Instagram account @buttonscarvesbeauty. This study used qualitative textual analysis using the theory of sensory representation systems by Vaknin (2008). This study showed that there were 300 data found. 70 (23.3%) data as visual, 16 (5.3%) data as auditory, and 214 (71.4%) data as kinaesthetic. NLP sensory representation system has benefits in making marketing communications more effective and also helps simplify communication messages so that the messages can be conveyed well to the consumers. Celebrity endorsement Nagita Slavina has a very significant impact on consumers in providing responses. It is hoped that the results of this research will be useful for everyone who wants to study sensory representation systems.